Prevalence and maternal factors associated with preterm birth at Teaching Hospital Anuradhapura, Sri Lanka - Dharmadasa, U.K.; Premathilake, S.M.S.P.; Kamalarupan, L.; Sathees, S. (University of Jaffna, 2024)
Introduction: Preterm birth is one of the primary causes of newborn morbidity and mortality. Preventing preterm birth is the public health importance worldwide. The aim of the study is to determine the prevalence and associated factors with preterm birth at Teaching Hospital Anuradhapura, Sri Lanka. Objective: To assess the prevalence and maternal factors associated with preterm birth at Teaching Hospital Anuradhapura, Sri Lanka. Methodology: This hospital-based descriptive cross–sectional study was conducted at three postnatal wards, Obstetrics and Gynecology unit at Teaching Hospital Anuradhapura. Data was collected from all the mothers admitted to the postnatal wards (n=597) following delivery from 1st October to 1st November 2023 by using an interviewer-administered questionnaire. The results were analyzed by chi-square test and Fisher exact using SPSS version 23. Results: Preterm birth prevalence was 9.54%. Most of the mothers (80.6%) were between the ages of 20-34 years. Of them 99.7% were married and 78.2% of mothers were housewives. Pregnancy complications such as Prelabor Rupture of Membrane, Pregnancy Induced Hypertension, placental abruption, oligohydramnios, cervical incompetence, chorioamnionitis, and vaginal candidiasis were significantly associated (P= 0.094; 98% CI) with preterm birth. Mode of delivery, presence of multiple gestation, previous history of preterm labour, Previous history of Gestational Diabetes Mellitus, consanguinity, had stressful events during pregnancy were also significantly associated with preterm birth (P<0.05). Age, marital status, level of education, family income, gravidity, anaemia, antenatal care visits, pre-conceptional folic acid usage, interpregnancy interval, and sexually transmitted diseases were not significantly associated with preterm birth. Conclusion: The prevalence of preterm birth was 9.54%. Some factors related to preterm delivery were identified in this study. It is recommended that improving pregnant women's health status may serve as a protective factor for reducing preterm births in future.
Keywords: Preterm birth; Pregnancy complications; Teaching Hospital Anuradhapura